Neuropsychological mechanisms underlying reading and writing disorders in primary school children - A. S. Sableva (Русский журнал детской неврологии, 2021)
Background. There has been an increasing interest to the diagnostics of learning difficulties in primary school children, which is associated with scientific advances in the interdisciplinary paradigm and high prevalence of difficulties with writing among children. Long-term observations demonstrate the presence of neuropsychological disorders in children with reading and writing disorders, which, in our opinion, necessitates further investigation in the interdisciplinary clinical and pedagogical aspect.Objective: to perform factor analysis of the mechanism underlying initial development of the disorder and its dynamics, to identify its types considering the development factor in the context of mastering the educational material.Materials and methods. This study included 10 children of 2nd-5th forms who visited specialists for the first due to learning difficulties.Results. We have identified several neuropsychological factors that caused problems with writing, including kinetic factor; factor of deliberate regulation of mental activity; modal-specific factors; kinesthetic factor; spatial factor; neurodynamic factor; simultaneous and successive factors; factor of interhemispheric interaction. The most common were the neurodynamic factor and the factor of interhemispheric interaction. We also observed signs of disorders in the deep parts of the brain, subcortical structures in the form of diffuse stem symptoms (in 2 cases, electroencephalography showed diffuse changes in the bioelectric activity of the brain with signs of irritation of the subcortical-diencephalic structures, in particular, synchronization of the main rhythm). We have identified a number of symptoms (primarily originating from the subcortex), such as general decrease in pace, problems with starting to work, rapid fatigue, decreasing productivity, an increase in the number of kinetic and auditory-speech difficulties, and spatial deficits.Conclusion. The lack of specially organized management in children with neuropsychological syndrome reinforces reading and writing disorders and leads to aggravation and alteration of symptoms during learning. Understanding of neuropsychological mechanisms underlying reading and writing disorders and their course is crucial for differential diagnosis, therapy, and comprehensive correction.